Fabrication of Solar-Powered Pumped-Storage Hydroelectric Power Station - Wahid, S M Taseen; Tasmiha, Samiha; Sabid, Zayed Al; Afif, Ahmed (MIST International Journal of Science and Technology, 2024)
Renewable energy is now accepted as the preferred alternative for electricity generation and as the replacement for fossil fuels. Worldwide demand for energy derived from renewable resources, especially hydro energy, is rising in tandem with rising fuel prices and environmental concerns. Our power station aims to harness the renewable energy potential of solar and hydroelectric power, combining them in an innovative and efficient manner. The prototype power station incorporates two main components: solar photovoltaic (PV) arrays and a pumped storage hydroelectric system. The solar PV arrays consist of a network of solar panels that capture sunlight and convert it into electricity. The generated solar power is used for both immediate consumption and for pumping water to a higher elevation. Efficiency and efficacy differ substantially between the values obtained from upstream and downstream. Significantly surpassing downstream, upstream generates 30W of electricity at 20V of voltage and 1.5A of current. By comparison, downstream has to work with a voltage of 42mV, a current of 0.04A, and a power production of just 0.00168W. These differences amply show that the upstream arrangement makes better use of solar energy. As such, upstream proves to be the superior choice for using solar energy because of its increased productivity and performance. MIJST, Vol. 12, June 2024 : 29-34 DOI: https://doi.org/10.47981/j.mijst.12(01)2024.445(29-34)